CHI study: protocol for an observational cohort study on ageing and mental health in community-dwelling older adults. Issue 5 (4th May 2020) - Lee, Rachael Zhi Yi; Yu, Junhong; Rawtaer, Iris; Allen, Patrick Finbarr; Bao, Zhiming; Feng, Lei; Feng, Qiushi; Lee, Jeong Kyu; Lim, Chin Tat; Ling, Lieng Hsi; Thang, Leng Leng; Naing, Thet; et al.
Abstract : Introduction: Ageing is associated with a multitude of healthcare issues including dementia, depression, frailty, morbidity associated with chronic disease and high healthcare utilisation. With Singapore's population projected to age significantly over the next two decades, it has become increasingly important to understand the disease burden and etiological process among older adults. The Community Health and Intergenerational study aims to holistically examine ageing in place by investigating the resilience and vulnerability factors of the ageing process in the biological, psychological and social domains within the environment. Methods and analysis: Using a cohort multiple randomised controlled trial design, comprehensive health profiles of community-dwelling older adults will be collected. The objective is to recruit 1000 participants (aged 60–99 years) living in the western region of Singapore within a period of 3 years (2018–2020). Assessments include basic sociodemographic, physical health and function (cardiac, oral and blood profiles and visual function), cognitive functioning, daily functioning, physical fitness, emotional state, free-flowing speech, sleep quality, social connectedness, caregiver burden, intergenerational communication, quality of life, life satisfaction, attitudes to ageing and gratitude and compassion. Results from the cohort will enable future studies to identify at-risk groups and develop interventions to improve the physical and mental health and quality of life of older adults. Ethics and dissemination: Approval of the cohort study by the National University of Singapore Institutional Review Board (NUS-IRB Reference code: H-17-047) was obtained on 12 October 2017. Written consent will be obtained from all participants. Findings from the cohort study will be disseminated by publication of peer-reviewed manuscripts, presentations at scientific meetings and conferences with local stakeholders.